Reciclagem de embalagens flexíveis multicamadas - Barbosa, Felipe Dantas (Universidade Federal de São Carlos, 2022)
Packaging industry is facing an important paradox in flexible plastic packaging for fresh food. While, food waste is avoided using multilayer and multi-material structures with barrier properties, that increase shelf life and preserve the product until its consumption, these packaging structures introduce important technical challenges for mechanical recycling due to the immiscibility between its components. This work aimed to assess the recyclability and the use of a compatibilization agent as a technical solution for end-of-life of a multilayer flexible films with immiscible polymers such as polyethylene (PE), polyamide (PA) and random copolymer of ethylene vinyl alcohol (EVOH). Recycled cast films with or without compatibilization agent were produced from the processing of multilayer film through a reactive extrusion in a twin-screw extruder to obtain an immiscible polymer blend with good physical-mechanical performance that can be used in high value packaging applications. The presence of reactive groups was evaluating being either originated from the compatibilizer or in the adhesive polymer, used to join the discrete layers of immiscible polymers during the production of multilayer film. Cast films were characterized in regarding its to morphology, rheological, thermal, thermo-dynamic-mechanical and mechanical properties. The morphology obtained in all formulations was a continuous matrix with a dispersed phase of the core-shell type, where EVOH encapsulates PA phase. The incorporation of compatibilizer proved to be efficient to reduce the particle size of the dispersed phase and the interfacial tension between the components. The mechanical properties of cast films suggest that there was an optimal concentration of compatibilizer between 2.5 and 5% in weight. Results also indicated that the coextrusion adhesive used during the production of multilayer film contained functional groups that were available to promote a compatibilization effect during the recycling process of multilayer film.
Multilayer flexible packaging recycling
Keywords: Embalagem multicamadas; Reciclagem; Compatibilização reativa; Multilayer packaging; Recycling; Reactive compatibilization; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA